Development of coalescents for paints and varnishes based on ionic liquids – the products of diethanolamine and inorganic acids interaction - Levchenko, Yevhenii; Sverdlikovska, Olga; Chervakov, Denys; Chervakov, Oleh (Eastern-European Journal of Enterprise Technologies, 2021)
This paper reports the synthesis of ionic liquids through the interaction between diethanolamine and orthophosphate and boric acids in order to establish the possibility of replacing volatile coalescents in a formulation for paints and varnishes with ionogenic compounds. The results from studying the influence of polymeric coalescents based on ionic liquids on the rheological properties of water-dispersion paints and varnishes of different nature are presented. It has been established that the synthesized coalescents could be used to modify the properties of paints and varnishes based on polyurethane and styrene-acrylic aqueous dispersions. It has been shown that the product of the interaction between diethanolamine and boric acid in aqueous solutions forms an ionogenic complex compound with a unipolar conductivity in terms of ОН─ ions. It was also established that when introduced to the formulation of water-dispersion paints and varnishes, the solutions of modifiers produce a diluting action. The influence of ionic liquids on the process of film formation of aqueous dispersions of polymers and pigmented paints and varnishes based on them was investigated. It was established that the synthesized ionogenic compounds are not inferior, in terms of their effectiveness, to the widespread conventional industrial coalescents of the Texanol→ type. Therefore, there is reason to assert the possibility of replacing the industrial coalescent Texanol→ in the formulation of pigmented water-dispersion paints and varnishes based on styrene-acrylic and polyurethane dispersions with fundamentally new synthesized ionogenic modifiers. Thus, the coatings with a coalescent based on ion liquid of diethanolamine borate have a higher level of conditional hardness, which exceeds by 17 % the hardness index of the paint made on the basis of the conventional Texanol→ type coalescent, without changing its decorative properties, such as color and shine